2007
DOI: 10.1007/s11102-007-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Progressive improvement of impaired visual acuity during the first year after transsphenoidal surgery for non-functioning pituitary macroadenoma

Abstract: Objective Improvement of visual field defects continues even years after the initial surgical treatment. Because this process of continuing improvement has not been documented for visual acuity, we audited our data to explore the pattern of recovery of visual acuity until 1 year after transsphenoidal surgery for nonfunctioning pituitary macroadenoma. Design Retrospective follow-up study. Patients Forty-three patients (mean age 56 ± 14 years), treated by transsphenoidal surgery for non-functioning pituitary mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 25 publications
2
37
0
2
Order By: Relevance
“…This is due to our early visual field assessment of the patient than the other authors and needs of long term follow-up. Improvement of visual field defects is a continuing process for at least 1 year 12,5,7 . Kerrison et al 2000 7 , showed progressive improvement of visual fields even more than 2 years after surgical decompression of the optic chiasm.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to our early visual field assessment of the patient than the other authors and needs of long term follow-up. Improvement of visual field defects is a continuing process for at least 1 year 12,5,7 . Kerrison et al 2000 7 , showed progressive improvement of visual fields even more than 2 years after surgical decompression of the optic chiasm.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection remains the initial treatment of choice for symptomatic non-prolactin-secreting pituitary macroadenomas 7,8 . Surgery offers the advantages of pathologic confirmation, immediate decompression of the optic apparatus, and rapid reduction of pathologic hormone secretion 7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgery offers the advantages of pathologic confirmation, immediate decompression of the optic apparatus, and rapid reduction of pathologic hormone secretion 7,9 . Long-term tumour control rates after surgery alone range between 50% and 80% 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In case of visual field defects, transsphenoidal surgery is the treatment of choice, resulting in the improvement of visual function in the majority of patients (1). Selected patients require treatment by postoperative radiotherapy (2).…”
Section: Introductionmentioning
confidence: 99%